Mediterranean diet impact on cardiovascular diseases: a narrative review. Issue 12 (December 2017) - Mattioli, Anna V.; Palmiero, Pasquale; Manfrini, Olivia; Puddu, Paolo E.; Nodari, Savina; Dei Cas, Alessandra; Mercuro, Giuseppe; Scrutinio, Domenico; Palermo, Pietro; Sciomer, Susanna; Di Francesco, Simona; Novo, Giuseppina; et al.
Abstract : N/A: Cardiovascular disease (CVD) accounts for more than 17 million deaths per year worldwide. It has been estimated that the influence of lifestyle on CVD mortality amounts to 13.7% for smoking, 13.2% for poor diet, and 12% for inactive lifestyle. These results deeply impact both the healthy status of individuals and their skills in working. The impact of CVD on productivity loss accounts for the 24% in total costs for CVD management. Mediterranean diet (MedD) can positively impact on natural history of CVD. It is characterized by a relatively high consumption of inexpensive and genuine food such as cereals, vegetables, legumes, nuts, fish, fresh fruits, and olive oil as the principal source of fat, low meat consumption and low-to-moderate consumption of milk, dairy products, and wine. Its effects on cardiovascular health are related to the significant improvements in arterial stiffness. Peripheral artery disease, coronary artery disease, and chronic heart failure are all positively influenced by the MedD. Furthermore, MedD lowers the risk of sudden cardiac death due to arrhythmias. The present narrative review aims to analyze the effects of MedD on CVD.